THE HISTORY OF RESEARCH AND DEVELOPMENT OF FAST PYROLYSIS PLANT FOR BIO-OIL PRODUCTION AT THE FACULTY OF AGRICULTURAL ENGINEERING OF UNICAMP - CORTEZ, LUIS A. B.; JORDAN, RODRIGO A.; B. JR., RICARDO; PEREZ, JUAN M. M.; ROCHA, JOSÉ D. (Revista Brasileira de Engenharia de Biossistemas, 2009)
This article is dedicated to describe the fast pyrolysis plant of biomass PPR-200 settled at UNICAMP School of Agricultural Engineering (FEAGRI). This fast pyrolysis plant, the first in Brazil to produce oil with fluidized bed reactor , began operating in 1998 with studies in a reactor for gasification, adapted to obtain bio-oil. Currently, PPR-200 operates with a 200 kg h-1 biomass capacity, and is used to conduct exploratory testing with various vegetable raw materials, such as sugar cane trash and bagasse, elephant grass, sawdust from wood, rice straw, coffee straw, orange bagasse, etc.. Around 15% of biomass is burnt to provide heat to the process. The remainder turns into the following products: bio-oil (20-40%), fine charcoal (20-30%), extract acid (10-15%) and pyrolysis gas (15-35%). The pyrolysis gas is composed mainly by CH4, the H2, CO and CO2.